Providing safe and effective pleural medicine services in the UK: an aspirational statement from UK pleural physicians. Issue 1 (3rd August 2018) - Evison, Matthew; Blyth, Kevin G; Bhatnagar, Rahul; Corcoran, John; Saba, Tarek; Duncan, Tracy; Hallifax, Rob; Ahmed, Liju; West, Alex; Pepperell, Justin Charles Thane; Roberts, Mark; Sivasothy, Pasupathy; et al.
Abstract : Physicians face considerable challenges in ensuring safe and effective care for patients admitted to hospital with pleural disease. While subspecialty development has driven up standards of care, this has been tempered by the resulting loss of procedural experience in general medical teams tasked with managing acute pleural disease. This review aims to define a framework though which a minimum standard of care might be implemented. This review has been written by pleural clinicians from across the UK representing all types of secondary care hospital. Its content has been formed on the basis of literature review, national guidelines, National Health Service England policy and consensus opinion following a round table discussion. Recommendations have been provided in the broad themes of procedural training, out-of-hours management and pleural service specification. Procedural competences have been defined into descriptive categories: emergency, basic, intermediate and advanced. Provision of emergency level operators at all times in all trusts is the cornerstone of out-of-hours recommendations, alongside readily available escalation pathways. A proposal for minimum standards to ensure the safe delivery of pleural medicine have been described with the aim of driving local conversations and providing a framework for service development, review and risk assessment.